AI-Assisted Health Information Seeking and Mothers’ Preparedness for Pediatric Emergencies: The Roles of Trust, Perceived Usefulness, and Information Verification - Danur Azissah R Sofais; Handi Rustandi; Dulce Elda Ximenes dos Reis; Firman Oswari (Media of Health Research, 2025)
Artificial intelligence (AI) has increasingly become a source of health information for parents, yet its role in supporting preparedness for pediatric emergencies remains unclear. This study examined the relationships between dimensions of AI-assisted health information seeking and mothers’ preparedness for pediatric emergencies. A cross-sectional survey was conducted among 385 mothers with children aged 0–12 years in Indonesia. Data were collected through an online questionnaire measuring AI-assisted health information seeking, including frequency of use, trust in AI, perceived usefulness, and information verification, as well as preparedness for pediatric emergencies. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression in IBM SPSS Statistics version 27. Information verification showed the strongest positive association with preparedness, whereas frequency of AI use demonstrated only a weak correlation.. Multiple linear regression revealed that information verification was the strongest predictor of preparedness (β = 0.41, p < 0.001), followed by perceived usefulness (β = 0.18, p < 0.001) and trust in AI (β = 0.12, p = 0.004). Frequency of AI use was not significantly associated with preparedness (p = 0.102). The model explained 38% of the variance in preparedness scores. Mothers’ preparedness for pediatric emergencies is influenced more by critical engagement with AI-generated information than by the frequency of AI use. Strengthening AI literacy and information verification skills may enhance the safe and effective use of AI in child health decision-making.